Pharmacovigilance of artemether-lumefantrine in pregnant women followed until delivery in Rwanda - Rulisa, Stephen (BioMed Central, 2012)
BACKGROUND: The World Health Organization presently recommends Artemisinin-based combination therapy (ACT) as first-line therapy for uncomplicated P. falciparum malaria. Many malaria-endemic countries, including Rwanda, have adopted these treatment guidelines. The Artemisinin derivative Artemether, in combination with lumefantrine, is currently used in Rwanda for malaria during the second and third trimesters of pregnancy. Safety data on the use of ACT in pregnancy are still limited though and more data are needed. METHODS: In this pharmacovigilance study, the exposed group (pregnant women with malaria given artemether-lumefantrine), and a matched non-exposed group (pregnant women without malaria and no exposure to artemether-lumefantrine) were followed until delivery. Data were collected at public health centres all over Rwanda during acute malaria, routine antenatal visits, after hospital delivery or within 48 hours after home delivery. Information gathered from patients included routine antenatal and peri-partum data, pregnancy outcomes (abortions, stillbirths, at term delivery), congenital malformations and other adverse events through history taking and physical examination of both mothers and newborns. RESULTS: The outcomes for the total sample of 2,050 women were for the treatment (n = 1,072) and control groups (n = 978) respectively: abortions: 1.3% and 0.4%; peri-natal mortality 3.7% and 2.8%; stillbirth 2.9% and 2.4%; neonatal death [less than or equal to]7 days after birth 0.5% and 0.4%; premature delivery 0.7% and 0.3%; congenital malformations 0.3% and 0.3%. A total of 129 obstetric adverse events in 127 subjects were reported (7.3% in the treatment group, 5.0% in the control group). In a multivariate regression model, obstetric complications were more frequent in the treatment group (OR (95% CI): 1.38 (0.95, 2.01)), and in primigravidae (OR (95% CI) 2.65 (1.71, 4.12) and at higher age (OR per year: 1.05 (1.01-1.09). CONCLUSIONS: There were no specific safety concerns related to artemether-lumefantrine treatment for uncomplicated falciparum malaria in pregnancy. However, more obstetric complications were observed in the treatment group. These increased occurrence of complications could, however, be caused by the malaria episode itself, but further assessment is required.